Manajemen Anestesi pada Neonatus dengan Atresia Oesophagus - Adi, Danis Woro Kuncoro; Sari, Djayanti; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2018)
A 12-day-old male neonate diagnosed with atresia oesophagus type C was planned to undergo decompression gastrostomy and feeding jejunostomi surgery. The patient’s mother complained that her child always vomit when given breast milk and said the child’s stomach was bloated. Patient was born from G1P1A0 mother with a history of aterm pregnancy, history of routine ANC, birth through normal delivery in midwife with clear amniotic fluid and APGAR SCORE 7/9. Birth weight 2382 grams and body weight is now 2282 grams. Anesthesia management performed under general anesthesia with conscious intubation technique ET No. 2.5 uncuff facilitate with 5mg ketamine. Maintenance anesthesia with O2, air, and sevoflurane. hemodynamics are stable during surgery. The operation lasts for 45 minutes. After the surgery is completed the patient is again treated at the NICU.